THE INFLUENCE OF HUMAN RESOURCES ON THE INCOME OF SMALL AND MEDIUM ENTERPRISES IN GALANG DISTRICT OF DELI SERDANG REGENCY: (Case Study of Rumah Makan Tenda Biru) - Sayang Khairani; Rahmat Suryanto Pirngadi (Teunuleh Publisher, 2021)
Rumah Makan Tenda Biru one of the largest restaurants in Galang district of Deli Serdang district, this restaurant provides Javanese and typical Minang cuisine. This business continues to grow over time, where at the beginning of the establishment of the building is only a small tent, and at this time already has a large building. The purpose of this study is to look at the influence of human resources on the income of Blue House, what problems are faced, and analyze consumer behavior. The results showed that, the location of human resources is very influential on the income of small and medium-sized businesses, by employing employees of graduates of High School (SMA) this business is able to reap profits of Rp. 105.000.000/month or Rp. 3.500.000 per day, when compared to when their employees graduated from Junior High School (SMP), the turnover obtained was only 60.000.000/month. In the time of the pandemic, there was a decrease in income, where before the pandemic profits reached Rp. 135.000.000/month. The obstacle experienced is the high PPH burden and must be paid every year for Rp 10.500.000. An analysis of consumer behavior states that 48% of consumers choose food as the main reason to visit the Tenda Biru Restaurant, 25% choose cleanliness, 15% choose service and 12% choose a vehicle parker place.